Barbie & Ken’s Struggle for Self-Discovery as Seen in the Film Barbie (2023) - Ayuning Dyah Kenza Pramita; Sindhy Sintya Mianani (Jurnal Ilmu Multidisiplin, 2025)
This research is titled "Barbie & Ken's Struggle for Self-Discovery as Seen in the Film Barbie (2023)" and focuses on the identity crisis and social expectations experienced by the characters Barbie and Ken in Barbie (2023). The research aims to understand how the characters face social pressure and struggle to find their true selves in a world full of gender stereotypes. However, a socially dynamic environment can cause a person to experience a crisis of self-confidence or an identity crisis, affecting their presence in public spaces. The research employ’s identity theory and Barbie Culture by Mary Rogers, which highlights the influence of the real world on perceptions of identity and gender roles. The qualitative analysis method applied includes direct observation of the narrative, dialogue, and visual elements in the film. The results reveal that Barbie and Ken undergo a complex identity journey, grappling with internal and external conflicts, including societal pressures that influence their self-perception. This research concludes by emphasizing the importance of more inclusive narratives in popular media to reflect the complexity of human identity and broaden understanding of how popular culture shapes views on gender and identity.